Metal organic framework film with shape-selective separation performance and preparation method and application thereof
By combining copper hydroxide nanowires with H2TCPP, a Cu-TCPP metal organic frame membrane was prepared, which solved the problem of insufficient selectivity in the separation of substances with similar molecular weight but different structures, and achieved efficient shape-selective separation performance.
Patent Information
- Application Number
- CN202411699710.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The existing nanofiltration membranes are not selective in separation of substances with similar molecular weight but different structures, making it difficult to achieve efficient separation.
The copper hydroxide nanowire was used to bind to medium-tetrakis(4-carboxyphenyl)porphine (H2TCPP) as a ligand to form a Cu-TCPP metal organic frame membrane, and prepared on the surface of the polyacrylonitrile ultrafiltration membrane support by in-situ growth method.
The preparation of an ultra-thin two-dimensional MOF film has been achieved, with a clear structure and pore size, and can efficiently retain substances with similar molecular weights but different structures, showing good shape selection and separation performance.
Smart Images

Figure CN119565413A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanofiltration membrane separation, and in particular to a metal organic framework membrane with shape-selective separation performance, a preparation method and application thereof. Background Art
[0002] Molecular separation using energy-saving and environmentally friendly membrane separation technology is crucial in the field of water environment, such as wastewater reuse, seawater and brackish water desalination. Currently, polymers are by far the most widely used membrane materials, mainly because they are easy to process and low cost. However, traditional polymer membranes used for water treatment usually have dense selective layers, resulting in insurmountable permeability. At the same time, existing nanofiltration membranes are not selective enough for substances with similar molecular weights but different structures, making it difficult to achieve efficient separation of substances with different molecular structures.
[0003] Metal-organic framework (MOF) materials are one of the research hotspots in the field of membrane separation. MOF materials have high specific surface area and porosity, diverse types and structures, and strong structural designability and pore size adjustability. They have more advantages in designing appropriate membrane materials for specific separation systems. In particular, two-dimensional MOF materials have significant advantages in preparing nanofiltration membranes with both high permeability and high selectivity. However, most of the existing two-dimensional MOF membranes are based on the suction filtration assembly of two-dimensional nanosheets, and the stacking of nanosheets will have an uncontrollable effect on the channel size in the membrane. In contrast, MOF membranes prepared based on the in situ growth method have a clear structure and pore size, and have more advantages in regulating separation selectivity. However, the in situ preparation of two-dimensional ultra-thin MOF membranes is still one of the difficulties in the field of membrane separation.
[0004] Therefore, it is urgent to conceive a new method to improve the above problems. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a metal organic framework membrane with shape selective separation performance and a preparation method and application thereof.
[0006] The present invention is achieved through the following technical solutions: A metal organic framework membrane with shape-selective separation performance is provided. The metal organic framework membrane is formed by combining copper hydroxide nanowires as a precursor and meso-tetra(4-carboxyphenyl)porphine (H2TCPP) as a ligand on the surface of a polyacrylonitrile ultrafiltration membrane support.
[0007] The present invention also provides a method for preparing the metal organic framework membrane with shape selective separation performance, comprising the following steps: S1: Dissolve copper nitrate trihydrate and aminoethanol in ultrapure water respectively, mix, stir for 5 minutes, and age for 2 days to obtain a copper hydroxide nanowire solution; S2: placing the polyacrylonitrile ultrafiltration membrane in a 2 mol / L sodium hydroxide aqueous solution at 65°C for 2 h for hydrolysis, and then washing it with ultrapure water until the pH is neutral to obtain a hydrolyzed polyacrylonitrile ultrafiltration membrane; S3: filtering the copper hydroxide nanowire solution obtained in step S1 onto the hydrolyzed polyacrylonitrile ultrafiltration membrane support obtained in step S2 to form a copper hydroxide nanowire precursor layer; S4: The ultrafiltration membrane with the copper hydroxide nanowire precursor layer obtained in step S3 is immersed in the H2TCPP solution, and after a period of reaction, it is taken out and placed in a vacuum oven for drying to obtain a metal organic framework membrane.
[0008] Copper nitrate trihydrate will dissociate in water to generate copper ions. Aminoethanol is a weak base that can partially dissociate in water to form hydroxide ions and react with copper ions. In the mixed solution, copper ions react with hydroxide ions to form copper hydroxide precipitates. Copper hydroxide may spontaneously grow along specific crystal planes through slow aging (2 days) to form a one-dimensional nanowire structure. Ultrapure water is used to ensure that the system is free of impurities. Short-term stirring (5 minutes) after uniform mixing helps to form a uniform initial system, but excessive stirring may destroy the formation of nanostructures.
[0009] Through the hydrolysis reaction under strong alkaline conditions, the cyano group in the polyacrylonitrile ultrafiltration membrane is converted into a negatively charged carboxyl group, which can enhance the interaction with the positively charged copper hydroxide nanowires and strengthen the bonding between the precursor layer and the support. The hydrolysis temperature is 65°C. Too high a hydrolysis temperature may cause the physical structure of the membrane to be destroyed and affect the mechanical strength. The increase in time and alkali concentration will deepen the degree of hydrolysis, but excessive hydrolysis may make the membrane too fragile or increase the pore size, affecting the separation performance. The hydrolyzed membrane is washed with ultrapure water until the pH value reaches neutral. This is to remove the residual sodium hydroxide on the surface of the membrane to avoid its impact on subsequent use.
[0010] Furthermore, in step S1, the concentration of copper nitrate trihydrate is 4 mmol / L, and the concentration of aminoethanol is 1.4 mmol / L. 4 mmol / L copper nitrate provides a moderate copper ion concentration, which helps to uniformly generate copper hydroxide nanowires. If the copper ion concentration is too low, the reactants in the reaction system are insufficient, and it is difficult to form continuous and uniform nanowires; if the concentration is too high, the reaction rate is too fast, forming irregular particles or aggregates instead of one-dimensional nanowires.
[0011] The concentration of aminoethanol is 1.4mmol / L, which provides a moderate alkaline environment: if the concentration of aminoethanol is too low, the alkalinity of the system is insufficient, the amount of copper hydroxide generated is small and irregular particles may be formed; if the ratio is too high and the alkalinity is too strong, it may cause the reaction rate to be too fast, forming irregular aggregates or porous structures. The concentration of 1.4mmol / L is moderate and will not cause violent reactions or local supersaturation of the solution, which is conducive to the formation of stable one-dimensional nanostructures. Under this alkaline condition, nanowires can slowly and preferentially grow along specific crystal planes, obtain good crystal integrity, and form longer one-dimensional structures (several microns in length). At the same time, the moderate reaction rate helps the dispersion of nanowires and reduces the aggregation effect.
[0012] The concentration of copper ions and the alkaline conditions provided by aminoethanol match each other, ensuring a moderate reaction rate while avoiding disordered morphology caused by oversaturation. The moderate reaction rate allows the crystals to grow slowly in a specific direction, ensuring the uniformity of the nanowires.
[0013] Preferably, in step S3, the volume of the copper hydroxide nanowire solution, i.e., the filtration volume, is 35.5 mL, and the effective filtration area of the supporting polyacrylonitrile ultrafiltration membrane is 7.065 cm 2 .
[0014] Preferably, in step S4, the solvent used to prepare the H2TCPP solution is a mixed solvent of ethanol and water, and the volume ratio of ethanol to water is 60:40. The mixed solvent of ethanol and water in a volume ratio of 60:40 is selected to balance the solubility, reaction uniformity and film quality of H2TCPP. This ratio provides a suitable organic and polar environment, which can enhance the solubility and stability of H2TCPP and optimize the structural properties and preparation process of the film.
[0015] Preferably, in step S4, the concentration of the H2TCPP solution is 0.025 mg / mL.
[0016] Preferably, in step S4, the reaction time is 4 hours and the vacuum oven drying temperature is 35°C.
[0017] During the reaction, H2TCPP molecules need to fully coordinate with the copper ions on the surface of the support to form a uniform metal organic framework (MOF) layer. According to the kinetics of the coordination reaction, 4 hours can provide enough time for the reaction to reach a near equilibrium state and ensure the integrity of the framework structure. Too short a time may lead to incomplete coordination reaction, insufficient surface coverage of the membrane or structural instability. Too long a reaction time may lead to excessive deposition on the surface of the membrane material or the formation of an irregular layered structure, thereby affecting the flux performance and selectivity of the membrane. Long-term solution immersion will also damage the mechanical strength of the support membrane.
[0018] The invention also provides application of the metal organic framework membrane in separation of dye molecules.
[0019] The present invention also provides application of the metal organic framework membrane in separation of metal ions in different valence states.
[0020] The advantages and beneficial effects of the present invention are as follows: 1. The present invention uses copper hydroxide nanowires as precursors, combines them with H2TCPP ligands to generate Cu-TCPP metal organic framework films, regulates the growth of MOF by the concentration of H2TCPP ligands, and successfully prepares ultra-thin two-dimensional MOF films in situ. The preparation method is simple and easy to scale up and prepare on a large scale.
[0021] 2. The Cu-TCPP metal organic framework membrane in the present invention is prepared based on the in-situ growth method, and the channel size in the membrane is clear (about 0.90 nm in the length direction and about 0.45 nm in the width direction, the structural pore size of the Cu-TCPPMOF material). It can efficiently retain non-planar molecules with larger cross-sectional sizes among molecules with similar molecular weights, and has a lower retention rate for planar molecules with smaller cross-sectional sizes, and has better shape-selective separation performance.
[0022] 3. The Cu-TCPP metal organic framework membrane of the present invention can effectively intercept trivalent metal ions with a larger hydration radius, while the interception rate for monovalent and divalent metal ions is relatively low, and has application potential in the separation of trivalent metal ions / monovalent and divalent metal ions. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic diagram of the film-forming process of the reaction between copper hydroxide nanowires and ligand H2TCPP of the present invention; Figure 2 is a surface scanning electron microscope image of the Cu-TCPP film prepared in Example 1; Figure 3 is a cross-sectional scanning electron microscope image of the Cu-TCPP film prepared in Example 1; Figure 4 is a bar graph of the water permeation flux and Safranin T rejection results of the Cu-TCPP membranes prepared in Examples 1-6; Figure 5 is the interception performance of the Cu-TCPP membrane prepared in Example 1 for different dyes; Figure 6 This is a pore structure diagram of the Cu-TCPP membrane prepared in Example 1. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0025] The invention provides a metal organic framework membrane with shape-selective separation performance. The metal organic framework membrane is formed by combining copper hydroxide nanowires as precursors and meso-tetra(4-carboxyphenyl)porphine (H2TCPP) as ligands on the surface of a polyacrylonitrile ultrafiltration membrane support.
[0026] The method for preparing the metal organic framework membrane with shape-selective separation performance comprises the following steps: S1: Dissolve copper nitrate trihydrate and aminoethanol in ultrapure water respectively, mix, stir for 5 minutes, and age for 2 days to obtain a copper hydroxide nanowire solution; S2: placing the polyacrylonitrile ultrafiltration membrane in a 2 mol / L sodium hydroxide aqueous solution at 65°C for 2 h for hydrolysis, and then washing it with ultrapure water until the pH is neutral to obtain a hydrolyzed polyacrylonitrile ultrafiltration membrane; S3: filtering the copper hydroxide nanowire solution obtained in step S1 onto the hydrolyzed polyacrylonitrile ultrafiltration membrane support obtained in step S2 to form a copper hydroxide nanowire precursor layer; S4: The ultrafiltration membrane with the copper hydroxide nanowire precursor layer obtained in step S3 is immersed in the H2TCPP solution, and after a period of reaction, it is taken out and placed in a vacuum oven for drying to obtain a metal organic framework membrane.
[0027] Schematic diagram of the film formation process of copper hydroxide nanowires reacting with ligand H2TCPP Figure 1 shown.
[0028] Example 1 S1: 0.8 mmol copper nitrate trihydrate and 0.28 mmol aminoethanol were dissolved in 200 mL ultrapure water respectively, mixed, stirred for 5 min, and aged for 2 days to obtain a copper hydroxide nanowire solution; S2: placing the polyacrylonitrile ultrafiltration membrane in a 2 mol / L sodium hydroxide aqueous solution, placing it in a 65°C oven for two hours, and then washing it with ultrapure water until the pH is neutral to obtain a hydrolyzed polyacrylonitrile ultrafiltration membrane; S3: 35.5 mL of the copper hydroxide nanowire solution obtained in step 1 was filtered onto the hydrolyzed polyacrylonitrile ultrafiltration membrane to form a copper hydroxide nanowire precursor layer. The filtration area of the polyacrylonitrile ultrafiltration membrane was 7.065 cm 2 ; S4: Dissolve 1 mg H2TCPP in 40 mL of ethanol / water mixed solvent, with the volume ratio of ethanol to water being 60:40, to form a ligand solution with a concentration of 0.025 mg / mL; then, place the ultrafiltration membrane with the copper hydroxide nanowire precursor layer face down into the H2TCPP ligand solution, take it out after reacting for 4 hours, and place it in a vacuum oven for drying at a drying temperature of 35°C to obtain the metal organic framework membrane.
[0029] Example 2 The difference between Example 2 and Example 1 is that in step 4, the concentration of the H2TCPP ligand is 0.100 mg / ml.
[0030] Example 3 The difference between Example 3 and Example 1 is that in step 4, the concentration of the H2TCPP ligand is 0.050 mg / ml.
[0031] Example 4 The difference between Example 4 and Example 1 is that in step 4, the concentration of the H2TCPP ligand is 0.010 mg / ml.
[0032] Example 5 The difference between Example 5 and Example 1 is that in step 4, the concentration of the H2TCPP ligand is 0.005 mg / ml.
[0033] Example 6 The difference between Example 6 and Example 1 is that in step 4, the concentration of the H2TCPP ligand is 0.001 mg / ml.
[0034] See also Figure 2 The metal organic framework membrane of the present invention is formed by using copper hydroxide nanowires as precursors and H2TCPP as ligands on the surface of a polyacrylonitrile ultrafiltration membrane support. H2TCPP is dissolved in a mixed solvent of ethanol and water to form a ligand solution. After contacting the copper hydroxide nanowire precursor, the copper hydroxide nanowire is gradually converted into Cu-TCPP to form a dense Cu-TCPP film layer. The surface and cross-sectional morphology of the Cu-TCPP membrane obtained in Example 1 are shown in FIG. Figure 2 and Figure 3 shown.
[0035] Test of the interception performance of the Cu-TCPP membrane obtained in Examples 1-6 The retention performance of the membrane was tested using a 0.1 g / L Safranin T aqueous solution at a pressure of 0.5 MPa. The test results are shown in Table 1 and Figure 4 As shown, it can be seen that the Cu-TCPP membrane obtained in Example 1 has the highest retention rate of Safranin T (95.75%), and the retention rates of the membranes at other concentrations are all lower. It can be seen that the preferred concentration of H2TCPP is 0.025 mg / mL.
[0036] Table 1. Test results of the interception performance of Cu-TCPP membranes obtained in Examples 1-6 Example 7 The interception test of different dyes by the Cu-TCPP membrane obtained in Example 1 The Cu-TCPP membrane prepared in Example 1 was tested under a pressure of 0.5 MPa using 0.1 g / L methyl blue, Congo red, chrome black T, methyl orange, methylene blue, safranin T and hematoxylin aqueous solution. The results are as follows: Figure 5 As shown, the results show that: The Cu-TCPP membrane has a retention rate of more than 99% for dyes with large molecular weight (greater than 400 g / mol) (methyl blue, Congo red, and chrome black T). For four dyes with relatively close molecular weights (safranin T, 350.85 g / mol; methyl orange, 327.33 g / mol; methylene blue, 319.85 g / mol; hematoxylin, 302.28 g / mol), the retention rates of non-planar molecules safranin T and hematoxylin are 95.75% and 96.69%, respectively, while the retention rates of planar molecules methyl orange and methylene blue are 59.50% and 70.03%, and hematoxylin with the smallest molecular weight has a higher retention rate than methyl orange and methylene blue.
[0037] Dyes with larger molecular weights are not easy to pass through the pores of the membrane due to their larger molecular size, and are therefore efficiently retained by the Cu-TCPP membrane. The molecules of these dyes are larger, causing them to be blocked by the pore screening effect in the membrane structure and unable to pass freely, thus showing a high retention rate (>99%). For the four dyes with smaller and similar molecular weights (Safranin T, Methyl Orange, Methylene Blue, and Hematoxylin), the difference in their retention rates is mainly related to the molecular structure (especially planarity) of the dyes: Safranin T (350.85 g / mol) and Hematoxylin (302.28 g / mol) are non-planar molecules, and the pore size ( Figure 6 The pores of the membrane are constrained by the pore size (in the middle and width direction) and are difficult to diffuse into the pores, thus having a higher retention rate (95.75% and 96.69% respectively). Methyl orange (327.33 g / mol) and methylene blue (319.85 g / mol) are planar molecules. The pore size is less constrained by the material, and the molecules are more likely to pass through the pores of the membrane, so the retention rate is low (59.50% and 70.03% respectively). Due to the above reasons, although hematoxylin has the smallest molecular weight (302.28 g / mol) among the above four dyes, the Cu-TCPP membrane described in Example 1 has the highest retention rate for it. In contrast, although the molecular weight of methyl orange and methylene blue is greater than that of hematoxylin, their planar structure makes them easier to pass through the membrane pores, resulting in a lower retention rate.
[0038] Example 8 Test on the interception of different metal ions by the Cu-TCPP membrane obtained in Example 1 Prepared 3+ 、Na + and Ca 2+The Cu-TCPP membrane was pretreated and cleaned, and the metal ion solution was filtered through the membrane at a pressure of 0.5 MPa. The retention rate of each ion was calculated. The results are as follows: 3+ The retention rate of ions is 81.26%, and the retention rate of monovalent Na + The retention rate of ions is only 21.08%, and the retention rate of divalent Ca 2+ The ion retention rate is 25.46%, and it has good separation ability of trivalent metal ions / monovalent and divalent metal ions.
Claims
1. A metal organic framework membrane with shape selective separation performance, characterized in that: The metal organic framework membrane is formed by combining copper hydroxide nanowires as precursors and meso-tetra(4-carboxyphenyl)porphine H2TCPP as ligands on the surface of a polyacrylonitrile ultrafiltration membrane support.
2. A method for preparing a metal organic framework membrane with shape selective separation performance as claimed in claim 1, characterized in that: The steps include: S1: Dissolve copper nitrate trihydrate and aminoethanol in ultrapure water respectively, mix, stir for 5 minutes, and age for 2 days to obtain a copper hydroxide nanowire solution; S2: placing the polyacrylonitrile ultrafiltration membrane in a 2 mol / L sodium hydroxide aqueous solution at 65°C for 2 h for hydrolysis, and then washing it with ultrapure water until the pH is neutral to obtain a hydrolyzed polyacrylonitrile ultrafiltration membrane; S3: filtering the copper hydroxide nanowire solution obtained in step S1 onto the hydrolyzed polyacrylonitrile ultrafiltration membrane support obtained in step S2 to form a copper hydroxide nanowire precursor layer; S4: The ultrafiltration membrane with the copper hydroxide nanowire precursor layer obtained in step S3 is immersed in the H2TCPP solution, and after a period of reaction, it is taken out and placed in a vacuum oven for drying to obtain a metal organic framework membrane.
3. The method for preparing a metal organic framework membrane with shape selective separation performance according to claim 2, characterized in that: In step S1, the concentration of copper nitrate trihydrate is 4 mmol / L, and the concentration of aminoethanol is 1.4 mmol / L.
4. The method for preparing a metal organic framework membrane with shape selective separation performance according to claim 3, characterized in that: In step S3, the volume of the copper hydroxide nanowire solution, i.e., the filtration volume, is 35.5 mL, and the effective filtration area of the supporting polyacrylonitrile ultrafiltration membrane is 7.065 cm 2 .
5. The method for preparing a metal organic framework membrane with shape selective separation performance according to claim 2, characterized in that: In step S4, the solvent used to prepare the H2TCPP solution is a mixed solvent of ethanol and water, and the volume ratio of ethanol to water is 60:
40.
6. The method for preparing a metal organic framework membrane with shape selective separation performance according to claim 2, characterized in that: In step S4, the concentration of the H2TCPP solution is 0.025 mg / mL.
7. The method for preparing a metal organic framework membrane with shape selective separation performance according to claim 2, characterized in that: In step S4, the reaction time is 4 hours, and the vacuum oven drying temperature is 35°C.
8. Use of the metal organic framework membrane with shape selective separation performance as claimed in claim 1 in the separation of dye molecules.
9. Use of the metal organic framework membrane with shape selective separation performance as claimed in claim 1 in separation of metal ions with different valence states.
Citation Information
Patent Citations
Method of rapidly preparing metal organic framework material thin-film from hydroxide nanowires and organic ligands under normal temperature
CN103059066A
Preparation method of metal organic framework material film as well as product and application of metal organic framework material film
CN103879066A
Polyamide thin-layer composite reverse osmosis membrane and preparation method and application thereof
CN111249920A
Cu (II)-tetra(4-carboxyphenyl)porphyrin membrane and preparation method thereof
CN112717730A
MOF-on-MOF composite membrane material and preparation method thereof
CN115627003A